Iconicity in instructional texts - Koch, Wolfgang (HERMES - Journal of Language and Communication in Business, 2008)
Diagrammatic iconicity is usually investigated at the surface syntactic level of texts. In this paper, I try to show that a meaningful concept of iconicity cannot be found on this level in non-trivial instructional texts. Instead, we have to dive deeper into semantic and conceptual structure. I present a model of Conceptual Structure that can cope with the demands that understanding an instructional text puts on the reader, and after analyzing a concrete text (a cooking recipe), I show that the concept of control structure is of essential importance for the description of the mapping between a conceptual model and a text. Control structures can be expressed explicitly through linguistic means or be inherent to the semantics of lexical predicates. In both cases, the presence of a dynamic conceptual model is necessary in order to establish iconicity relations between the text and the underlying mental representation.